2016
DOI: 10.1016/j.aap.2016.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect evaluation of a road safety education program based on victim testimonials in high schools in Belgium

Abstract: For several decades policy makers worldwide have experimented with testimonials as a strategy to promote road safety supportive views in a wide variety of target populations such as recidivists and students. In its basic format, a (relative of) a victim or an offender brings a personal testimonial of what it is to experience a traffic accident. The underlying idea is that such a testimonial will emotionally affect participants, thereby stimulating them to cognitively reflect upon their own behavior and respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 30 publications
3
19
2
Order By: Relevance
“…An effect evaluation measures the effect of the program in the target population by assessing the progress in the outcomes that the program set to achieve. The effect evaluation is performed either by observing behavior in a naturalistic setting [44], by checking the involvement of educated/trained participants in traffic accidents [45], or by investigating the change in the socio-cognitive and behavioral variables [46]. In this study, we investigated the change in socio-cognitive variables.…”
Section: Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…An effect evaluation measures the effect of the program in the target population by assessing the progress in the outcomes that the program set to achieve. The effect evaluation is performed either by observing behavior in a naturalistic setting [44], by checking the involvement of educated/trained participants in traffic accidents [45], or by investigating the change in the socio-cognitive and behavioral variables [46]. In this study, we investigated the change in socio-cognitive variables.…”
Section: Questionnairementioning
confidence: 99%
“…The TPB is one of the empirically most supported behavioral theories and has been validated in diverse research domains [54,55]. The TPB model has been used to evaluate road safety education programs to see changes in socio-cognitive variables because of the intervention [46,53,56]. Studies conducted in traffic safety have shown TPB to effectively explain intention to DUI [7,57], speeding [58,59], distractions [60,61] and other risk behaviors.…”
Section: Questionnairementioning
confidence: 99%
“…In other words, Education for Road Safety is more effective when there are consistent interventions on both socio-cognitive and behavioral issues (instead of isolated or single actions). This is especially true whenever the profile of their beneficiaries in terms of, e.g., age, gender and educational level are considered, in order to provide contents prone to be properly understood and applicable to a population's daily road-related activities, actual behaviors and potentially involved stakeholders, such as their parents and peers [33].…”
Section: The Park Model: Positive Attitudes Risk Perception and Knowmentioning
confidence: 99%
“…Recent evidence shows how the strengthening and promotion of safe (or protective) road behaviors among young road users can be substantially reinforced by means of different interventions and strategies related to Education in Road Safety (RSE) [10,16,33]; this is especially true if we consider that, even though young users' primary role on the road is that of pedestrians, they get progressively involved in driving tasks by using small (nonmotorized) vehicles such as bicycles and scooters. This represents, in most cases, a systematic transition towards the role of driver, which implies, in most countries, the necessity of attending road training and education programs provided by driving schools [13,36,39,40].…”
Section: Enhancing the Learning Of Safe Road Behaviors In Children: Tmentioning
confidence: 99%
“…The studies shown that one should act from both sides if we are to succeed in this type of education [36]. As well, it has been used other complimentary strategies in the road educational programs, such as the testimony of the victims, although it has not reached conclusive results about its effectiveness [37]. Road education in the classroom, at school, is (however) the most used strategy in the education in this field.…”
Section: Introductionmentioning
confidence: 99%